Caring Values in Islamic Religious and Moral Education on Merdeka Belajar Curriculum: A Study of Fifth-Grade Student and Teacher Books - Dodi Ilham; Diah Asdiany; Andi Husni Zainuddin; Nurdin K; Muhammad Iksan; Rustan Santaria; Wahyullah Alannasir (AL-ISHLAH: Jurnal Pendidikan, 2023)
The philosophy of the Merdeka Belajar curriculum, which emphasizes a learning approach focused on learners’ needs and potential, can strengthen caring values. This research analyzes the indicators for strengthening the value of caring in student and teacher books for Islamic religious and moral education. The research method used is a literature review. The study subjects are Islamic religious education and moral textbooks for Grade V in Sekolah Penggerak. The study found that the forms of strengthening the value of caring in the books only contain three sub-indicators: 1) affection, 2) empathy, and 3) sympathy. Based on these three sub-indicators, there are several benefits of strengthening the value of caring, including 1) improving the quality of student personality; 2) improving social skills; 3) increasing religious awareness, critical thinking skills, fostering positive attitudes towards learning, and improving the quality of life for learners. This research also recommends six forms of strengthening the value of caring educators, namely: 1) teaching the value of caring for the learner’s environment; 2) providing real-life examples to learners; 3) using learning methods that encourage learner care; 4) teaching the value of caring for others to learners; 5) appreciating caring behavior, and 6) teaching care for other living beings. Overall, this research contributes to the field of education by highlighting the importance of caring values in student and teacher books, suggesting practical implications for curriculum development, textbook evaluation, teacher training, student development, and future research endeavors.